Financial performance and its determinants: an analysis of the national Film Development Corporation Malaysia (FINAS) / Mohamad Bashir Veeran Kutty and Nur Hayati Hayazi - Veeran Kutty, Mohamad Bashir; Hayazi, Nur Hayati (Faculty of Business and Management, 2016)
The purpose of this research paper is to analyse the determinants of financial ratio that affecting the financial performance of National Film Development Corporation Malaysia (FINAS). Several of the financial ratios are selected to analyse FINAS Financial performance; Debt Ratio (DR) represent the leverage ratio, current ratio (CR) represent the liquidity ratios and account receivable turnover (ARTO) represent asset utilization ratios. This research paper discovers the relationship between the FINAS financial performance and three independent variables for 30 years starting the year 1984 to 2014 by using secondary data. A multiple linear regression was employed to study the relationship between the dependent variable and independent variables. The results show that DR and CR have the negative significant relationship with FINAS financial performance while ARTO has positive significant effect on the financial performance of FINAS. This research paper contributed the result of the effect financial ratios of FINAS as this is the first research on National Film Development Corporation Malaysia (FINAS).